Systems‐level thinking for nanoparticle‐mediated therapeutic delivery to neurological diseases. (25th August 2016) - Curtis, Chad; Zhang, Mengying; Liao, Rick; Wood, Thomas; Nance, Elizabeth
Abstract : Neurological diseases account for 13% of the global burden of disease. As a result, treating these diseases costs $750 billion a year. Nanotechnology, which consists of small (~1–100 nm) but highly tailorable platforms, can provide significant opportunities for improving therapeutic delivery to the brain. Nanoparticles can increase drug solubility, overcome the blood–brain and brain penetration barriers, and provide timed release of a drug at a site of interest. Many researchers have successfully used nanotechnology to overcome individual barriers to therapeutic delivery to the brain, yet no platform has translated into a standard of care for any neurological disease. The challenge in translating nanotechnology platforms into clinical use for patients with neurological disease necessitates a new approach to: (1) collect information from the fields associated with understanding and treating brain diseases and (2) apply that information using scalable technologies in a clinically‐relevant way. This approach requires systems‐level thinking to integrate an understanding of biological barriers to therapeutic intervention in the brain with the engineering of nanoparticle material properties to overcome those barriers. To demonstrate how a systems perspective can tackle the challenge of treating neurological diseases using nanotechnology, this review will first present physiological barriers to drug delivery in the brain and common neurological disease hallmarks that influence these barriers. We will then analyze the design of nanotechnology platforms in preclinical in vivo efficacy studies for treatment of neurological disease, and map concepts for the interaction of nanoparticle physicochemical properties and pathophysiological hallmarks in the brain. WIREs Nanomed Nanobiotechnol 2017, 9:e1422. doi: 10.1002/wnan.1422 This article is categorized under: Therapeutic Approaches and Drug Discovery > Nanomedicine for Neurological Disease Nanotechnology Approaches to Biology > Nanoscale Systems in Biology Abstract : For a nanoparticle‐based therapeutic delivery system to be effective in the brain, it must be able to overcome the collective system of barriers ‐ a nanoparticle must avoid rapid clearance from circulation and cross the blood‐brain barrier, and once in the brain, the nanoparticle must navigate the brain microenvironment, and provide site‐specific therapeutic action only at a diseased cell.